Makna Desain Maskot “Deri & Dara” Sebagai Simbol Pilkada Depok 2024 - Arik Azel Syahputra; Susilowati; Selvy Maria Widuhung (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study explores the meaning of the “Deri & Dara” mascot as a symbol of the 2024 Depok Regional Election using Charles Sanders Peirce’s semiotic approach. The mascot is considered a visual communication medium that represents local identity and democratic values. The research employed a descriptive qualitative method, with data collected through observation, documentation, and an in-depth interview with the mascot designer, Bayu Eko Nurtanto.The findings reveal that in terms of icon, the starfruit, nail, and ballot paper directly represent the election process. As an index, the mascot’s gestures reflect cheerfulness, courage, and confidence, while the starfruit philosophy symbolizes balance and healthy democratic growth. At the symbolic level, the names “Deri” (Depok Riang) and “Dara” (Pilkada Gembira), the Hobo typeface, and the colors yellow, green, red, and white communicate optimism and active citizen participation.This, “Deri & Dara” function both as a visual identity and as a political communication medium integrating local values with democratic spirit. Keywords: Meaning of Design, Mascot, Symbol, Semiotics Charles Sanders Abstrak Penelitian ini membahas makna desain maskot “Deri & Dara” sebagai simbol Pilkada Depok 2024 melalui pendekatan semiotika Charles Sanders Peirce. Maskot dipandang sebagai media komunikasi visual yang merepresentasikan identitas lokal dan nilai demokrasi. Metode yang digunakan adalah kualitatif deskriptif, dengan data diperoleh melalui observasi, dokumentasi, dan wawancara dengan desainer maskot, Bayu Eko Nurtanto. Hasil penelitian menunjukkan bahwa pada aspek ikon, belimbing, paku pencoblos, dan surat suara menjadi representasi langsung Pilkada. Pada aspek indeks, gestur tubuh maskot merefleksikan keceriaan, keberanian, dan kepercayaan diri, sementara filosofi belimbing melambangkan keseimbangan demokrasi. Pada aspek simbol, nama “Deri” (Depok Riang) dan “Dara” (Pilkada Gembira), tipografi Hobo, serta warna kuning, hijau, merah, dan putih mengomunikasikan optimisme serta partisipasi aktif masyarakat. Dengan demikian, maskot “Deri & Dara” berfungsi sebagai identitas visual sekaligus medium komunikasi politik yang mengintegrasikan nilai lokal dan semangat demokrasi. Kata Kunci: Makna Desain, Maskot , Simbol, Semiotika Charles Sanders Peirce